Study of a new code set in multi-rate CDMA VLC system - Jianping WANG; Danyang CHEN; Huimin LU; Jianli JIN; Lifang FENG (Tongxin xuebao)
For the diverse traffic requirements of the wireless communication multiple access system and the characteristics of VLC, a new orthogonal variable spreading factor zero cross correlation (OVSF-ZCC) code set was proposed for multi-rate VLC code division multiple access (CDMA) system, which consisted of unipolar spreading sequences with variable lengths, and zero cross correlation properties.Assuming the radiation of LED light source was Lambert distribution, a multi-rate CDMA-VLC system with proposed code set was further presented.The effects of construction parameters, transmission rate and distance on system performance were evaluated.The results show that the new code set can effectively reduce multiple access interference (MAI), and support multiple transmission rate requirements of different users in multiple access systems.